Tumor-Free Transplantation of Patient-Derived Induced Pluripotent Stem Cell Progeny for Customized Islet Regeneration. (17th March 2016) - El Khatib, Moustafa M.; Ohmine, Seiga; Jacobus, Egon J.; Tonne, Jason M.; Morsy, Salma G.; Holditch, Sara J.; Schreiber, Claire A.; Uetsuka, Koji; Fusaki, Noemi; Wigle, Dennis A.; Terzic, Andre; Kudva, Yogish C.; et al.
Abstract : Transplantation of progenitors from induced pluripotent stem cells reprogrammed by lentiviral vectors led to the formation of invasive teratocarcinoma-like tumors in more than 90% of immunodeficient mice. Combined transgene-free reprogramming and elimination of residual pluripotent cells by enzymatic dissociation ensured tumor-free transplantation, ultimately enabling regeneration of type 1 diabetes-specific human islet structures in vivo. Abstract: : Human induced pluripotent stem cells (iPSCs) and derived progeny provide invaluable regenerative platforms, yet their clinical translation has been compromised by their biosafety concern. Here, we assessed the safety of transplanting patient-derived iPSC-generated pancreatic endoderm/progenitor cells. Transplantation of progenitors from iPSCs reprogrammed by lentiviral vectors (LV-iPSCs) led to the formation of invasive teratocarcinoma-like tumors in more than 90% of immunodeficient mice. Moreover, removal of primary tumors from LV-iPSC progeny-transplanted hosts generated secondary and metastatic tumors. Combined transgene-free (TGF) reprogramming and elimination of residual pluripotent cells by enzymatic dissociation ensured tumor-free transplantation, ultimately enabling regeneration of type 1 diabetes-specific human islet structures in vivo. The incidence of tumor formation in TGF-iPSCs was titratable, depending on the oncogenic load, with reintegration of the cMYC expressing vector abolishing tumor-free transplantation. Thus, transgene-free cMYC-independent reprogramming and elimination of residual pluripotent cells are mandatory steps in achieving transplantation of iPSC progeny for customized and safe islet regeneration in vivo. Significance: Pluripotent stem cell therapy for diabetes relies on the safety as well as the quality of derived insulin-producing cells. Data from this study highlight prominent tumorigenic risks of induced pluripotent stem cell (iPSC) products, especially when reprogrammed with integrating vectors. Two major underlying mechanisms in iPSC tumorigenicity are residual pluripotent cells and cMYC overload by vector integration. This study also demonstrated that combined transgene-free reprogramming and enzymatic dissociation allows teratoma-free transplantation of iPSC progeny in the mouse model in testing the tumorigenicity of iPSC products. Further safety assessment and improvement in iPSC specification into a mature β cell phenotype would lead to safe islet replacement therapy for diabetes.